Jambore Majlis Taklim sebagai Media Aktualisasi Pemberdayaan Jamaah MT (Sebuah Upaya Pemberdayaan MT di Kec. Mustikajaya Kota Bekasi): Majlis Taklim’s Jamboree is an Empowerment Media Actualization of MT Worshipers (An Empowerment MT in Mustikajaya Bekasi City) - erti herlina (Jurnal Bimas Islam, 2014)
Religious community development efforts are planned, integrated and sustainable so that religious values can be fostered in the life of the nation, state, and society so as to create a life of peace, harmony and prosperity. Religious community development can be done in three patterns: recitations, Tazkiyah and study groups. The three patterns are example by the Prophet Muhammad in building civilized and dignified Medina community, it is signed by a life of peace, harmony, and prosperity which based on the religious values which is live and cultivated among the community. Religious community is a community-based typology of faith and piety. It is triggering disbursement of mercy and blessings from all corners that lead to prosperity, well-being and harmony of life. Reflected faith and piety that in everyday life become characteristic of the religious community that promises happiness and well- being in the world and afterlife. In a religious community development efforts can use the media and religious signs that lived, grew, and rooted in society, for example taklim. The most basic of coaching is to empower Majelis Taklim simultaneously. Among these steps is to conduct Majelis Taklim Jamboree. On the other hands, the form of innovation in guiding Majelis Taklim, Majelis Taklim jamboree is also serves as an evaluation media in guiding Majelis Taklim.